Addressing Misconceptions about Wildland-Urban Interface Issues - Martha C. Monroe (EDIS, 2005)
Residents in the wildland-urban interface probably have some notions about their local environment. They may have an experience, or may have heard something from neighbors, which helps them construct explanations and understandings that make sense to them. The challenge for extension agents and resource managers is to understand the beliefs that are interfering with the acceptance of new concepts, acknowledge them, show how they are incomplete, and help people restructure their mental models to accommodate the new information. Educators have to do this all the time, but it is a new technique for extension agents and resource managers. While it may be easiest to address misconceptions when speaking to an individual, it is important to consider how to use this concept when speaking to a group, when writing a newsletter article, or when talking to the media. This document is FOR 108, one of a series of the School of Forest Resources and Conservation Department, UF/IFAS Extension. First published November 2005.